Clinical features, laboratory findings and outcomes of in fants with hyperbilirubinaemia requiring exchange blood transfusion at Chris Hani Baragwanath academic hospital - Seake, Karabo Pertunia (My University, 2015)
Background: Severe hyperbilirubinaemia (SHB) requiring exchange blood transfusion (EBT) continues to be a problem despite use of anti-D immunoglobulin and kinder-gentle approach in its management. Knowing features of infants with SHB might assist in its prevention. Objectives: To determine features, presentation and outcome of infants with SHB. Methods: We conducted review of records of infants admitted at Chris Hani Baragwanath Academic Hospital with SHB requiring EBT in 2009-2013. Descriptive analysis of characteristics, clinical presentation, laboratory findings, and outcome at discharge was performed. Results: Out of 150 patients who received EBT, 101 (67.3%) had records available for review. The majority were born by normal vaginal delivery (86.1%), weighed ≥2500g (65.4%), exclusively breastfed (82%) and were outpatients (66.3%). A higher proportion of outpatients were born at clinic (68.7% vs 5.9%, p<0.001), vaginally (92.5% vs 73.5%, p=0.009), male (62.6% vs 38.3%, p=0.020), weighing ≥2500g (76.1% vs 44.1%, p=0.001) than inpatients. Median postnatal age at EBT was 5days. Clinical presentation was suggestive of acute bilirubin encephalopathy (ABE) in 25%. Among mother-infant pairs with known blood groups 70% and 9% had ABO- and Rh-incompatibility respectively. Common abnormal laboratory findings post-EBT were thrombocytopaenia (77%), hypercalcaemia (55%) and anaemia (36%). A total of six patients (6%) died, all within 7days of EBT, but none during EBT. Infants who died had a higher serum bilirubin than survivors (623±100 vs 498±136 mmols/l, p<0.001). Common causes of deaths were ABE (n=3) and sepsis (n=2). Conclusion The majority of patients with SHB were vaginal term births, exclusively breastfed from home or clinic-referrals, and had ABO incompatibility. SHB is associated with significant morbidity and mortality.
A research report submitted to the faculty of health Sciences, University of Witwatersrand, Johannesburg in partial fulfillment of the requirements for the degree of Master of Medicine in the branch of paediatrics and child health Johannesburg, 2015